Preeclampsia and Sleep-Disordered Breathing: A Case-Control Study - Facco, Francesca L. (2013)
OBJECTIVE: To determine whether sleep-disordered breathing (SDB) is more prevalent among women with preeclampsia than among normotensive controls STUDY DESIGN: Preeclamptic patients admitted to the hospital for observation and normotensive, gestational age matched controls hospitalized for obstetrical indications other than preeclampsia were recruited for an overnight sleep evaluation. Watch-PAT100, a validated wrist-mounted, ambulatory device designed to diagnose SDB, was used to complete all sleep studies. RESULTS: Twenty preeclamptic patients and 20 controls were recruited. Preeclamptic subjects had a higher mean BMI (32.6± 9.5 vs. 24.5 ± 3.5, P=0.001). Preeclamptic subjects had higher mean respiratory disturbance (RDI, mean difference 4.9 events/hour of sleep), apnea hypopnea (AHI, mean difference 5.7 events/hour of sleep) and oxygen desaturation (ODI, mean difference 4.5 events/hour of sleep) indices, however these differences did not reach statistical significance. Preeclamptic subjects were more likely to have more severe forms of SDB compared to controls (ODI ≥ 5, 20% vs. 0%, p=.047). CONCLUSION: Compared to normotensive controls, preeclamptic subjects experience more SDB events and a greater degree of nocturnal hypoxemia. Further research is needed to determine if SBD, independent of BMI, is a significant contributing factor to the risk of developing preeclampsia